Anticancer Activity of Phospholipid-Dexibuprofen Conjugates Loaded in Nanostructured Lipid Carriers - Thiruchenthooran V; Świtalska M; Maciejewska G; Palko-Łabuz A; Bonilla-Vidal L; Espina M; Luisa Garcia M; Wietrzyk J; Souto EB; Sánchez-López E; Gliszczyńska A (International Journal of Nanomedicine, 2025)
Vaikunthavasan Thiruchenthooran,1 Marta Świtalska,2 Gabriela Maciejewska,3,4 Anna Palko-Łabuz,5 Lorena Bonilla-Vidal,6,7 Marta Espina,6,7 Maria Luisa Garcia,6,7 Joanna Wietrzyk,2 Eliana B Souto,8 Elena Sánchez-López,6,7 Anna Gliszczyńska1 1Department of Food Chemistry and Biocatalysis, Wrocław University of Environmental and Life Sciences, Wrocław, Poland; 2Department of Experimental Oncology, Ludwik Hirszfeld Institute of Immunology and Experimental Therapy, Polish Academy of Sciences, Wrocław, Poland; 3Central Laboratory of the Instrumental Analysis, Wrocław University of Technology, Wrocław, Poland; 4Omics Research Center, Wrocław Medical University, Wrocław, Poland; 5Department of Biophysics and Neuroscience, Wrocław Medical University, Wrocław, Poland; 6Department of Pharmacy, Pharmaceutical Technology and Physical Chemistry, University of Barcelona, Barcelona, Spain; 7Institute of Nanoscience and Nanotechnology (IN2UB), University of Barcelona, Barcelona, Spain; 8UCD School of Chemical and Bioprocess Engineering, University College Dublin, Belfield, Dublin 4, D04 V1W8, IrelandCorrespondence: Anna Gliszczyńska, Email anna.gliszczynska@upwr.edu.pl Elena Sánchez-López, Email esanchezlopez@ub.eduPurpose: In our work, we focused on the development of nanostructured lipid carriers (NLCs) loaded with dexibuprofen (DXI) and their application for cancer therapy by proposing the binding of phospholipids with this non-steroidal anti-inflammatory drug (NSAID) to obtain new delivery systems.Methods: We successfully synthesized seven conjugates with good yields, four of which are new, and have not been previously published in the literature. The structures of the obtained conjugates were confirmed and comparative in vitro studies of their antiproliferative activity were conducted, along with molecular modeling to assess their therapeutic potential.Results: 1-DXI-2-hydroxy-sn-glycero-3-phosphocholine (DXI-LPC), 1-DXI-2-oleoyl-sn-glycero-3-phosphocholine (DXI-OA-PC) and 1-oleoyl-2-DXI-sn-glycero-3-phosphocholine (OA-DXI-PC) showed selectivity for cancer cells, influencing the cell cycle and inducing apoptosis. Encapsulation of heterosubstituted conjugates with increased lipophilic character in NLC resulted in DXI-PA-PC-NLC and DXI-OA-PC-NLC with favorable size (around 150 nm) and polydispersity index of 0.15, high encapsulation efficacy (above 99%), long-term stability, and modified release profile (51.4% and 48.9% of DXI released from DXI-PA-PC-NLC and DXI-OA-PC-NLC, respectively). Antiproliferative assays confirmed enhanced activity of synthesized products and their increased accumulation in cancer cells.Conclusion: This study describes the synthesis of new conjugates of DXI and phospholipids and their nanotechnological formulations for potential use in cancer therapy. Keywords: dexibuprofen, phospholipids, nanostructured lipid carrier, lipid nanoparticles, anticancer properties